Is the Rule of Halves Still Relevant today? A Study from a Tertiary Care Hospital in India - Sajjan Shivani; Parvinder S. Chawla; Khyati Kalra (Preventive Medicine: Research & Reviews, 2024)
Introduction: Hypertension significantly increases the risk of heart disease, stroke and kidney failure. It impacts approximately one-third of adults in Southeast Asia, yet a considerable number remain unaware or lack access to adequate treatment. Introduced by Wilber and Barrow in 1972, the ‘rule of halves’ governs the prevalence of hypertension. The study aimed to re-evaluate the rule of halves and suggest measures for early detection and treatment compliance. Materials and Methods: A hospital-based study was conducted from (August, 2023 to October, 2023) involving 1518 employed individuals selected through non-probability sampling, excluding those seriously ill or absent. Data were gathered through a semi-structured questionnaire. Results: Out of all 1518 study subjects, 206 (14%) were diagnosed with hypertension. Among them, (42) 20% were aware and within this aware group, 81% received treatment. Of those receiving treatment (25), 73% received treatment adequately. Conclusion: The findings suggest that, although the proportion of diagnosed hypertension was lower, the rates of treatment and adherence amongst individuals with diagnosed hypertension were higher. There is a need to revisit the rule of halves for India.